Problemas monetarios argentinos - Liliedal, Augusto M. (1961)
The Argentine monetary system was established by law Nº 1030 in 1881. This law adopted the bimetallism gold and silver, a system which was short lived, barely lasting two years until law 1354 disposed that the banks should only issue notes payable in national gold pesos, thus following the system of the countries of the Latin Union. A far reaching event was the creation of the Conversion Bank in 1890, an activity which was to last 45 years, and to which the country is indebted for its outstanding services. The object of its existence was the conversion (exchange of gold to notes) and the withdrawal of gold in circulation. In response to the necessity of carrying out a monetary security programme, in 1935 law 12155 created the Central Bank. It was not formed as an official entity, its aim being to assure independence from political powers. However, in 1946, due to contrary ideas, the Central Bank was nationalized together with the deposits of the commercial banks. When the Central Bank was created it had the exclusive privilege of issuing notes, but was obliged to maintain a minimum metallic reserve, thus responding to the ideas of that time, where metallic guarantee was considered to be the firmest support of currency value. Now days on the contrary it is considered to be a system in decline. However, money issuing should be limited in accordance with BENDIXEN'S words "Issue new money when progress of economic life increases production and withdraw it from circulation when production decreases".